Testimony and Autobiography: Towards a Concept of Narrative Testimonials of the Self in Film and Literature of Argentina Postdictatorship - Bartalini, Carolina C. (2021)
Throughout the years that followed the democratic reopening, there have been different ways of figuring out the experiences of the victims of the last Argentine civil-military dictatorship (1976-1983) in cinema and literature. Between the testimonial discourse and the autobiography procedures, a new proliferating multimedia genre opens up from the 21st century: the testimonial narratives of the self. In them, peculiar and innovative aesthetic-political forms of addressing the experiences of memory of the second generation of the state genocide are configured, the explorations of cinema, literature and the photography of the generation of the daughters and sons of disappeared people.